2019
DOI: 10.3390/su11154068
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis of Actors and Policy Keywords for Sustainable Environmental Governance: Focusing on Chinese Environmental Policy

Abstract: Environmental issues are viewed as a serious problem with a complex network structure involving various stakeholders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…After being analyzed by period, during the 11th FYP period, six words (enterprise, tradition, Beijing, economy, region, and architecture) were identified that emphasized the centrality of a strong connection between words rather than the importance of frequency. These words are termed essential keywords, and they exert a strong influence on discourse (Zhang et al, 2019). During this period, the discourse was characterized by an emphasis on tradition and regional characteristics, development centered on Beijing, and economic development, together with the role of companies in this.…”
Section: Empirical Analysis Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After being analyzed by period, during the 11th FYP period, six words (enterprise, tradition, Beijing, economy, region, and architecture) were identified that emphasized the centrality of a strong connection between words rather than the importance of frequency. These words are termed essential keywords, and they exert a strong influence on discourse (Zhang et al, 2019). During this period, the discourse was characterized by an emphasis on tradition and regional characteristics, development centered on Beijing, and economic development, together with the role of companies in this.…”
Section: Empirical Analysis Resultsmentioning
confidence: 99%
“…Network analysis is an appropriate methodology for exploring a society's micro/ macro characteristics comprising networks. When data derived from text mining are applied to network analysis, various patterns and structures appearing in the text network can be identified and used to analyze policy discourse (Zhang et al, 2019). In this study, we examined the text sets gathered from websites using text mining techniques to determine which words appear and spread socially within different periods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast with the Western model of neoliberal governance, which emphasizes 2 of 17 individualism over collective responsibility, the leading role in formulating and implementing environmental regulations in China has always been taken on by different governmental levels; non-state actors in China mainly depend on government authority to exert their influence in managing environmental problems [8,9]. Additionally, local governments play a vital role in solving local environmental problems by responding to the policies of national and provincial governments [10][11][12].…”
Section: Introductionmentioning
confidence: 99%